Reconstructing Eco-Maqāṣid al-Sharī‘ah for CSR Policy and Radioactive Waste Management: An SDGs-Based Study in Banten and West Java - Titik Triwulan Tutik; Kunawi Basyir; Mahtumridho Ghufron Bin Simun; Jauharoti Alfin; M. Suyudi (Al-Manahij: Jurnal Kajian Hukum Islam, 2026)
Radioactive waste management is not only a technical and administrative concern but also an ethical, ecological, and intergenerational responsibility. This article reconstructs the concept of eco-maqāṣid al-sharī‘ah as a normative framework for strengthening corporate social responsibility (CSR) policies in radioactive waste management in Banten and West Java, Indonesia. Existing regulatory frameworks tend to prioritize procedural compliance, risk control, and institutional administration, while giving limited attention to moral accountability, ecological justice, and community-based responsibility. Using a normative legal method supported by conceptual and policy analysis, this study examines statutory regulations, corporate reports, international safety standards, and relevant Islamic legal literature. The findings show that eco-maqāṣid, particularly the protection of life, future generations, and the environment, offer a transformative ethical foundation for developing Sharia-based CSR in radioactive waste governance. The cases of Banten and West Java demonstrate the urgency of integrating Islamic environmental ethics into risk mitigation, public transparency, community participation, and corporate accountability. The study’s main novelty lies in proposing Eco-Sharia Governance, a maqāṣid-based policy model that bridges national legal frameworks, international radioactive waste standards, SDGs 3, 6, 12, and 13, and Islamic ethical values. This model contributes to a more holistic approach to radioactive waste management by shifting CSR from mere corporate obligation toward ecological responsibility, public safety, and intergenerational justice